Generic solutions for consistency problems in multi-scale traffic flow models - Analysis and preliminary results - Joueiai, Mahtab; van Lint, Hans; Hoogendoorn, Serge (Proceedings (IEEE Conference on Intelligent Transportation Systems), 2013)
Multi-scale traffic models aim to describe traffic operations in transportation networks by combining and connecting different representations of traffic flows (microscopic, macroscopic) along with the corresponding spatial representations (links, nodes at different levels of aggregation) and temporal scales (discrete time steps) in a single framework. Multi-scale modelling is an increasingly important research subject, particularly in the design and evaluation of large scale ITS, since these may affect travel and driving behaviour at different scales, ranging from route choice behaviour to (ontrip) path planning and actual driving behaviour. In such applications, the consistency of travel and traffic operations between the different models in a multi-scale framework is critically important. In this paper we provide a new taxonomy that enables the identification of the sources of inconsistency between traffic flow models of different scales. We show that these inconsistencies can be categorised into two main categories, which we term global and local inconsistency respectively. Since these two classes relate to the endogeneity or exogeneity of the variables and parameters of interest, two models connected in a multi-scale framework can be both locally and/or globally inconsistent. On the basis thereof we sketch two main solution directions targeted at resolving both classes of inconsistencies. In this paper we demonstrate the applicability of both solution directions with an example case. We close with a discussion on the further development of a multi-scale modelling framework based on these results.